Zdeňka Havlíčková: Tochter der Nation fabulosa (Theatrum historiae, 2012)
The historical and literary works that emerged about Zdeňka Havlíčkova illustrate to what extent the interpretation of the destiny of an individual is affected both by the author who undertakes the theme and by the overall context of the society.
Keywords: biography; nationalism; national collections and lotteries